Thiopurine-mediated impairment of hematopoietic stem and leukemia cells in Nudt15R138C knock-in mice - Tatsumi, Goichi; Kawahara, Masahiro; Imai, Takayuki; Nishishita-Asai, Ai; Nishida, Atsushi; Inatomi, Osamu; Yokoyama, Akihiko; Kakuta, Yoichi; Kito, Katsuyuki; Andoh, Akira (Leukemia, 2020)
Thiopurines are widely used as antileukemia agents and immunosuppressants. Recent large-scale clinical studies revealed a strong association between the NUDT15 p.Arg139Cys ( NUDT15 R139C ) polymorphism and severe thiopurine-induced leukocytopenia. We established knock-in mice harboring p.Arg138Cys ( Nudt15 R138C ), which corresponds to the human polymorphism. A clinically relevant dose of mercaptopurine (MP) induced lethal cytopenia in Nudt15 R138C -harboring mice. MP dose reduction attenuated the hematopoietic toxicity, phenocopying clinical observations and providing Nudt15 genotype-based tolerable doses of MP. High-dose MP induced acute damage to hematopoietic stem and progenitor cells (HSPCs) in Nudt15 R138C/R138C mice. A competitive transplantation assay revealed that not only Nudt15 R138C/R138C HSPCs, but also Nudt15 +/R138C HSPCs suffered stronger damage than Nudt15 +/+ HSPCs, even by lower-dose MP, after long-term administration. In a Nudt15 genotype-based posttransplantation leukemia recurrence model generated by bone marrow replacement with congenic wild-type cells and a small number of leukemia stem cells, MP prolonged the survival of mice with posttransplantation Nudt15 R138C/R138C leukemia recurrence. In conclusion, our model will facilitate NUDT15 genotype-based precision medicine by providing safer estimates for MP dosing, and our findings highlighted the high susceptibility of hematopoietic stem cells to MP and suggested that exploiting thiopurine toxicity might be a novel treatment approach for leukemia in NUDT15 R139C -harboring patients.